Transformation of biomass into carbon nanofiber for supercapacitor application – a review - Vo, Dai-Viet N.; Elfina, Azwar; Wan Adibah, Wan Mahari; Joon, Huang Chuah; Nyuk, Ling Ma; Wei, Haur Lam; Su, Shiung Lam (Elsevier, 2018)
This paper starts with a review on challenges and need of improved supercapacitor application, which is then followed by advantages of biomass compared with other materials for use in supercapacitor application. The conversion of biomass into carbon nanofiber using different techniques was extensively reviewed for its advantages and limitations. It was revealed that the materials currently used are yet to be fully sustainable or feasible for energy storage application. In contrast, biomass represents a widely available and sustainable material to be converted into carbon nanofiber for energy storage application. Different techniques were employed for carbon nanofiber production to achieve different objectives, comprising high product yield, feasible diameter adjustment, low electric consumption, and shorter production time. Nevertheless, it was revealed that many key properties of the biomass-derived carbon nanofiber have yet to be fully investigated, as there are still knowledge gaps to be filled for each technique. Thus, more studies are needed to broaden the existing understanding in the key parameters of different techniques in order to develop a highly desirable carbon nanofiber from biomass for sustainable energy storage application.